Biochar reduces the toxicity of silver to barley (Hordeum vulgare) and springtails (Folsomia candida) in a natural soil - Mocová, Klára Anna; Petrová, Šárka; Pohořelý, Michael; Martinec, Marek; Tourinho, Paula S (Environmental science and pollution research international, 2022)
The use of biochar in soil remediation is a promising method to deal with metal contamination. In the present study, the influence of biochar amendment on the toxicity of silver (as AgNO3) to terrestrial organisms was assessed. For this, toxicity tests were conducted with terrestrial plant barley (Hordeum vulgare) and invertebrate springtails (Folsomia candida) in the standard natural Lufa soil amended or not with a wood-derived biochar at 5% (w/w). Biochar addition increased root length and mass in barley, compared to unamended soil. However, the effects of Ag on barley growth were masked by a great variation among replicates in biochar-amended soil. Photosynthetic pigment contents (total chlorophyll and carotenoids) were lower in plants exposed to Ag in Lufa soil, but not in biochar-amended soil. Moreover, Ag drastically decreased dehydrogenase activity in Lufa soil. For springtails, the addition of biochar clearly decreased the toxicity of Ag. The LC50 was 320 mg Ag/kg in Lufa soil, while no mortality was observed up to 500 mg Ag/kg in biochar-amended soil. The EC50 for effects on reproduction was significantly higher in biochar-amended soil compared to unamended Lufa soil (315 and 215 mg Ag/kg, respectively). The wood-derived biochar used in this study has shown a potential for remediation of contaminated soils, as a decrease in Ag toxicity was observed in most endpoints analysed in barley and springtails.
Keywords: Plants; Arthropods; Soil contamination; Hordeum; Heavy metals; Soil invertebrates; Soil Pollutants; látky znečišťující půdu; půda; Dehydrogenase activity; zvířata; Silver; členovci; stříbro; Ecotoxicology; ječmen (rod); Animals; Soil; Charcoal; dřevěné a živočišné uhlí